Implementation of Strategic Management in the Legislative Function of Commission I of the Bungo Regency DPRD - Zahsyi, Muhammad; Ermaini, Ermaini; Suryani, Ade Irma (PT. BERBAGI TEKNOLOGI SEMESTA, 2025)
Changes in the composition of political party seats in the Bungo Regency Regional People's Representative Council (DPRD) over the past three periods reflect local political dynamics that directly influence the legislative function, particularly in Commission I, which oversees governance, law, and legislation. This study aims to analyze the development of political party seat distribution in the 2014-2019, 2019-2024, and 2024-2029 periods, and examine its implications for the implementation of strategic management in the legislative function. The method used is descriptive analysis with a qualitative approach, utilizing legislative election results data from official sources and a review of Bungo Regency DPRD documents. The results show a significant shift in political power, with several parties experiencing an increase in the number of seats, such as NasDem, Demokrat, Gerindra, and PKB, while other parties such as Golkar, PKS, PPP, and PBB experienced a decrease. The number of parties holding seats decreased from 13 to 10 in the last period, indicating a consolidation of political power. These findings emphasize the importance of implementing strategic management that includes coalition-based legislative planning, strengthening legislative capacity, and effective political coordination mechanisms to ensure that legislative products are more responsive, inclusive, and oriented towards the public interest.